2016
DOI: 10.1016/j.chb.2016.06.060
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of factors associated with Game Transfer Phenomena severity

Abstract: Game Transfer Phenomena (GTP) (i.e. altered perceptions, spontaneous thoughts and behaviors with game content) occur on a continuum from mild to severe. This study examined the differences between mild, moderate and severe levels of GTP. A total of 2,362 gamers' participated in an online survey. The majority of gamers experienced mild levels of GTP. The factors significantly associated with severe levels of GTP were: (i) being students,(ii) being aged 18 to 22, (iii) being professional gamers, (iv) playing vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 52 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…Consequently, it can be cautiously assumed that individuals with high cognitive instability may have more difficulty in refraining from thinking about the videogame despite doing other things. In this context, previous research [127] reported that GTP are associated with PVG. However, it should be noted that GTP are a broader issue related not only to the negative aspects of videogames playing but also to the positive aspects [128].…”
Section: Plos Onementioning
confidence: 84%
“…Consequently, it can be cautiously assumed that individuals with high cognitive instability may have more difficulty in refraining from thinking about the videogame despite doing other things. In this context, previous research [127] reported that GTP are associated with PVG. However, it should be noted that GTP are a broader issue related not only to the negative aspects of videogames playing but also to the positive aspects [128].…”
Section: Plos Onementioning
confidence: 84%
“…Accordingly, GTP can be manifested as altered sensorial perceptions including the experience of bodily sensations within video games (Ortiz de Gortari and Griffiths 2015). Additionally, severe levels of GTP has been associated with long gaming sessions and dysfunctional patterns of gaming because those with severe levels of GTP share characteristics with profiles of disordered gamers (Ortiz de Gortari et al 2016). Although the regression models indicated overall SP, as well as its three sub-aspects, were significantly associated to IGD behaviors, the four LGM models calculated were not suggestive of either the overall SP or its three sub-dimensions (experienced) being significantly associated with IGD behaviors variations during the 3-month period examined.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2015 study of 2,362 gamers, Ortiz de Gortari, now at the University of Liège in Belgium, and her coauthors reported that 97% of the gamers reported having experienced GTP (12). And in a study published in 2016, she and her colleagues found that people with severe GTP are more likely to have problematic or addictive gaming habits (13).…”
Section: South Korea's Gaming Obsessionmentioning
confidence: 99%